Who will perform my autopsy? - Stephen A. Geller (University of São Paulo, 2014)
When I was a resident pathologist at The Mount Sinai Hospital, New York, from 1965 to 1969, we were taught that it was a privilege to perform an autopsy on another physician and particularly on another pathologist. I learned this particularly from Max Robinowitz, my chief resident, with whom I performed my first adult autopsy; a 71 year old physician with thymoma-associated myasthenia gravis whose proximate cause of death was bronchopneumonia.